2014
DOI: 10.5489/cuaj.1807
|View full text |Cite
|
Sign up to set email alerts
|

Baseline urologic surgical skills among medical students: Differentiating trainees

Abstract: Introduction: Urology training programs seek to identify ideal candidates with the potential to become competent urologic surgeons. It is unclear whether innate technical ability has a role in this selection process. We aimed to determine whether there are any innate differences in baseline urologic technical skills among medical students. Methods: Second-year medical students from the University of Toronto were recruited for this study and stratified into surgical and non-surgical cohorts based on their repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The review identified two dVSS cohort studies that assessed innate surgical ability among medical students [38,48]. One of these is also the only validity study in which participants executed all 26 basic core tasks of the Mimic software (Table 4) [38].…”
Section: Discriminant Validitymentioning
confidence: 99%
“…The review identified two dVSS cohort studies that assessed innate surgical ability among medical students [38,48]. One of these is also the only validity study in which participants executed all 26 basic core tasks of the Mimic software (Table 4) [38].…”
Section: Discriminant Validitymentioning
confidence: 99%
“…Urology trainees are not currently selected based on their technical expertise or manual dexterity. Gupta argues that the technical skills of aspiring trainees can be assessed in areas such as laparoscopy, robotics, and cystoscopy [2]. However, the definition of technical competence continues to be debated and few studies identify standard approaches that differentiate competent vs non-competent performers [3].…”
Section: Introductionmentioning
confidence: 99%